Manajemen Sumber Daya (MSD) Bimbingan dan Konseling pada Satuan Pendidikan Formal - Jarkawi Jarkawi; Husnul Madihah (Bulletin of Counseling and Psychotherapy, 2022)
The focus of this research is Human Resource Management in the field of guidance and counseling in formal education units by studying about human resource planning, recruitment, career development of guidance and counseling teachers. Furthermore, it focuses more on obstacles and support in the management of human resources, both for education unit leaders and even more so for guidance and counseling teachers. The purpose of this research is to cover; 1) Describe the management of human resources in the field of guidance and counseling in the formal education unit, 2) Clarify the description of HR planning, recruitment, career development in the field of guidance and counseling in the formal education unit, 3) Sharpen an in-depth picture of the obstacles in the management of Human Resources in the field of guidance and counseling in formal education, 4) Sharpen the description of the supporting factors in the management of Human Resources in the field of guidance and counseling in formal education. This research method is descriptive qualitative, namely to obtain information about human resource management in the field of guidance and counseling in formal education units in Banjarmasin City. Data Reduction Analysis, namely the Conclusion Data Display. Research Results (1). There is no preparatory stage (2) There has been no data collection for BK teachers (3) There has been no determination of BK teacher positions that are not too urgent (4) There is no planning or program development that helps in meeting the needs and duties of BK teachers. (5) There has never been an implementation or implementation of the planning for the needs of BK teachers.